Pengaruh Motivasi, Komunikasi dan Disiplin Kerja terhadap Kinerja Karyawan pada BPR Sadana - Diah Pratiwi, Ni Kadek; Astrama, I Made; Gede, I Komang (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Tight competition in business encourages every business actor to improve employee performance in order to compete and develop. Employee performance problems were also faced by BPR Sadana and based on the results of observations it was found that there were problems related to motivation, communication and work discipline. The aim of this research is to determine the influence of motivation, communication and work discipline on employee performance. This research was conducted at BPR Sadana with a population of 45 employees. This research uses census techniques so that all members of the population are involved as research subjects. Primary data collection was carried out using a questionnaire. Hypothesis testing is carried out using multiple linear regression. Based on the results of the analysis, it can be concluded that: 1) motivation has a positive and significant effect on employee performance, 2) communication has a positive and significant effect on employee performance, 3) work discipline has a positive and significant effect on employee performance and 3) motivation, communication and work discipline positive and significant effect on employee performance.